"Who Knows Me the Best and Can Encourage Me the Most?": Matching and Early Relationship Development in Youth-Initiated Mentoring Relationships with System-Involved Youth. Issue 1 (January 2019) - Spencer, Renée; Gowdy, Grace; Drew, Alison L.; Rhodes, Jean E.
Youth-initiated mentoring (YIM), in which youth select adults from within their communities to serve as mentors in relationships that are formalized through mentoring programs, has the potential to redress problems faced by many mentoring programs that could adversely affect system-involved youth, such as volunteer attrition and premature match closures. However, only a few programs have implemented YIM, and there is little research on this approach. This qualitative interview study examines the formation of YIM relationships and how they are experienced by mentors ( n = 14), youth ( n = 17), and the youths' parent/guardian ( n = 6). Youth tended to select adults whom they had encountered through school or social services. Findings indicate that the YIM selection process contributed to mentor, youth, and parent/guardian investment in the mentoring relationship and to the youth's rapid development of feelings of closeness and trust in the mentor. Knowing that mentors would be nonjudgmental, trustworthy, and dedicated appeared to facilitate positive relationship development, which is important given the difficulty of engaging and serving system-involved youth in mentoring programs.